3D architecture reduced graphene oxide-MoS2 composite: Preparation and excellent electromagnetic wave absorption performance. (November 2016) - Ding, Xiao; Huang, Ying; Li, Suping; Zhang, Na; Wang, Jianguo
Abstract: High-performance electromagnetic absorbers with wide absorption band, strong absorption and lightweight are necessary for industry and military application. To obtain the desired materials, two-dimensional (2D) atomic layers structure nanosheets, such as graphene and graphene-like, were adopted due to its unique structure and properties. Here, 3D architecture reduced graphene oxide-molybdenum disulfide (RGO-MoS2 ) composite was prepared by one-pot hydrothermal reaction. MoS2 generated on graphene oxide intercalation through hydrothermal process and rGO is obtained in the meanwhile. 3D architecture RGO-MoS2 composite can effectively prevent two-dimensional nanosheets re-stacked and can be applied in electromagnetic wave absorption field. In this paper, composites consist of RGO and various MoS2 were prepared and their electromagnetic performances were investigated for the first time. Maximum absorption bandwidth (RL < −10 dB) is 5.92 GHz with thickness of 2.5 mm. We may reasonably conclude that RGO-MoS2 composite can serve as excellent light-weight electromagnetic wave absorbers and can be widely used in practice.